Efektifitas Instagram Sebagai Strategi Promosi Online RJ Holiday - Januar Rezky; Lucky Adhitya (BTJ : Business and Technology Journal, 2024)
Instagram is a digital platform that is popular with all groups, whether for personal or business needs. Currently, the features offered by Instagram are various, starting from offering photo, video and even live broadcast features. Instagram itself also has a significant impact on people's lives, especially improving people's economic levels. Many business people use Instagram, one of which is the RJ Holiday Travel Business. RJ Holiday's use of Instagram itself is very good, but the content presented is still less creative than other Instagrams, so the content presented on RJ Holiday's Instagram is still not optimal. The method used in implementing this work program is that it uses a lot of analysis and observation methods regarding what types of content are suitable for publication and the results of the analysis and observations implemented are produced in the form of short videos which are displayed on RJ Holiday's own Instagram. The results of implementing independent content creation are expected to be able to open up new avenues for RJ Holiday in creating higher quality content and being able to understand what trends are happening in society so as to be able to attract audiences on RJ Holiday's Instagram and attract audience interest in using RJ's services. Holiday at a later date. Keywords:  travel agency,  Instagram, Trend,  Holiday, Personal and bussiness